Terrorist deradicalisation in global contexts : success, failure, and continuity - Gunaratna, Rohan, 1961- (New York : Routledge, 2020)
'A collection of case studies of terrorist rehabilitation programmes from around the world. This book examines the wide-ranging methodologies of terrorist deradicalisation initiatives adopted by different countries globally. It contextualises these programs as they were initiated and explains the factors that led to their relative success, failure or continuity. The different typology of rehabilitation modes acts a guide to establishing a framework and a starting point for any deradicalisation and rehabilitation programme. These case studies demonstrate practical examples of how the theories can be applied to achieve real results. An indispensable resource for researchers, practitioners and policy-makers in the field of Terrorist Deradicalisation and Rehabilitation'--
Includes bibliographical references and index.
Keywords: Terrorists -- Rehabilitation -- Case studies; Terrorism -- Prevention -- Case studies